Comparison of Efficacy of Oral Methotrexate and Acitretin for Generalized Lichen Planus - Mohib Ullah,; Hassan, Tahir; Tahir, Raheel; Humera, Farah; Rani, Nazish (Indus Journal of Bioscience Research, 2025)
Background: Generalized lichen planus is a chronic inflammatory dermatosis that often requires systemic therapy when widespread or resistant to topical treatment. Methotrexate and acitretin are commonly used systemic agents, but comparative data on their efficacy remain limited. Objective: To compare the efficacy of oral methotrexate versus oral acitretin in the treatment of generalized lichen planus. Material and Methods: This randomized controlled trial was conducted at the Dermatology Outpatient Department of Sheikh Zayed Hospital, Rahim Yar Khan, over six months (May 31, 2024 to November 30, 2024). A total of 124 patients aged 13–50 years with generalized lichen planus were included. Patients were randomly divided into two groups of 62 each. Group A received oral methotrexate 10 mg once weekly for 12 weeks along with folic acid, while Group B received oral acitretin 50 mg daily for 6 weeks. Efficacy was assessed clinically after completion of treatment. Data were analyzed using SPSS version 25.0, and the Chi-square test was applied to assess statistical significance (p ≤ 0.05). Results: Overall, efficacy was achieved in 48 (77.4%) patients treated with methotrexate and 35 (56.5%) patients treated with acitretin (p = 0.013). Stratified analysis showed significantly higher efficacy of methotrexate in females, patients aged ≥30 years, those with disease duration ≥6 months, BSA involvement ≥20%, and those with comorbidities. Conclusion: Oral methotrexate was significantly more effective than oral acitretin in managing generalized lichen planus and may be considered a preferable first-line systemic therapy, especially in patients with chronic or extensive disease.